Model of Indonesian Church Leadership in Responding to Digital Disruption - Evelyn Margareth Tedjapranata; Owen Sandjoto; Anugerah Morris; Manlian Ronald A. Simanjuntak (Scriptura Indonesia, 2026)
Digital transformation and globalization have significantly reshaped the paradigm of church leadership, particularly in the processes of leadership regeneration and multiplication, requiring churches not only to adapt to technological advancements but also to strategically integrate them into ministry practices. This study aims to analyze the factors influencing leadership multiplication within the church, evaluate the role of digital technology in discipleship and leadership development, and formulate relevant digital transformation strategies. The research employs a qualitative approach using a theological-descriptive method based on literature analysis, integrating perspectives from biblical leadership, transformational leadership, digital leadership, and leadership multiplication. The findings indicate that digital transformation can accelerate leadership multiplication; however, its effectiveness depends on a strong spiritual foundation, a paradigm shift in leadership, and a structured leadership development system. As a contribution, this study proposes the Transformational–Multiplicative Digital Leadership (TMDL) model, consisting of four main pillars as a strategic framework for developing adaptive, relevant, and sustainable church leadership in the digital era.